Ortnogonal-to-unitary ensemble crossover in the electronic specific heat of metal namoclusters - Mukhin, S.I.; Kurapova, O.V.; Moiseev, I.I.; Vargaftik, M.N.; Volokitin, Y.E.; Mettes, F.L.; Jongh, L.J. (Физика низких температур, 2001)
We present a theoretical and experimental study on the influence of a magnetic

field on the energy-level statistics in metal nanoparticles. Based on the random-matrix

theory, a gradual field-in-duced crossover behavior is predicted from the orthogonal to the

unitary ensemble. Experimental data of the electronic specific heat of metal nanoparticles

for different fields in the quantum-size temperature regime compare favourably with these

theoretical (analytical) predictions.